Pengaruh Net Profit Margin (Npm) Dan Debt To Equity Ratio (Der) Terhadap Harga Saham Pada Industri Food And Beverage - Nurlela Nurlela; Madjidainun Rahma (Universitas Malahayati, 2022)
In looking at the stock price of a company, there are several factors including Net Profit Margin and Debt to Equity Ratio. Therefore, this study aims to see whether these two variables have an effect on stock prices. The data in this study were taken from the annual reports of each company for 2016-2020. Purposive sampling was used in sampling. From the research results, it is known that the Net Profit Margin and Debt to Equity Ratio have the same effect on stock prices, either partially or simultaneously.